How changes to Irish healthcare financing are affecting universal health coverage. - Briggs, A (2013)
In 2010, the World Health Organisation (WHO) published the World Health Report - Health systems financing: the path to universal coverage. The Director-General of the WHO, Dr Margaret Chan, commissioned the report "in response to a need, expressed by rich and poor countries alike, for practical guidance on ways to finance health care". Given the current context of global economic hardship and difficult budgetary decisions, the report offered timely recommendations for achieving universal health coverage (UHC). This article analyses the current methods of healthcare financing in Ireland and their implications for UHC. Three questions are asked of the Irish healthcare system: firstly, how is the health system financed; secondly, how can the health system protect people from the financial consequences of ill-health and paying for health services; and finally, how can the health system encourage the optimum use of available resources? By answering these three questions, this article argues that the Irish healthcare system is not achieving UHC, and that it is unclear whether recent changes to financing are moving Ireland closer or further away from the WHO's ambition for healthcare for all.